2017
DOI: 10.1001/jamapsychiatry.2017.3047
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Depression Treatment in Primary Care

Abstract: clinicaltrials.gov Identifier: NCT01301859.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 47 publications
0
63
2
1
Order By: Relevance
“…On the contrary, an optimal medication adherence has been linked to positive clinical outcomes regardless of the antidepressant type (Thompson, Peveler, Stephenson, & McKendrick, ). Thus, favoring medication adherence is a real challenge for professionals involved in MD cares (Sirey et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, an optimal medication adherence has been linked to positive clinical outcomes regardless of the antidepressant type (Thompson, Peveler, Stephenson, & McKendrick, ). Thus, favoring medication adherence is a real challenge for professionals involved in MD cares (Sirey et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the prevalence of depression and anxiety in older adults do not offer insight into the explanatory models of illness (i.e., how they describe their experience, causes of depression and anxiety, and what to do about it) [9]. Interventions that take into account one's understanding of illness could lead to improved engagement and better health outcomes [10]. Approaches with a narrow focus or use of a bio-medical model may overlook important social, contextual, and cultural factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, depression response and remission and medication Apply evidence-based practices in a population health perspective, use a data-driven approach to assess and improve practice performance, and regularly evaluate outcomes, adverse events, and patients' perspectives to advance services use and adherence did not differ by group. Sirey and colleagues [17] showed that patients who engaged in a psychosocial intervention targeting antidepressant medication adherence were more likely to be adherent at 6 and 12 weeks than those receiving usual care. Although the intervention group exhibited a larger initial reduction in depressive symptom severity, symptom improvement was similar across groups at 24 weeks.…”
Section: Components Of Depression Treatment In the Pcmhmentioning
confidence: 99%